EKSETENSI LEGONG KERATON - I Wayan Mastra; Luh Putu Pancawati; Kadek Agung Sariwigna (LP3M Universitas PGRI Mahadewa Indonesia, 2022)
The Tradition and Exiestence of Legong Keraton. Legong Keraton or tradisional Legong as a cultural product of the past has undoubtedly contributed significantly to the development of orther dances in Bali. Legong Keraton with itsdifferent aestetic principles is different from theprevious dance genere, such as Gambuh.Traditional Legong has beokome the basis of new creation of Legong. Creation of Legong are also called as creations of Pelegongan because those creations use ceratain elements of the aestetic concepts of Lgong Keraton accumulated in the pelegongan concepts. Traitional Legong develops and continues to exist with new variants of Legong. The examination of Legong concept. Traditional Legong develops an continues to exist with new variants of Legong. The examination of Legong Keraton aims to understeand the characteristics of Legong Keraton that exist within the scope of traditional Legong Keraton aims to untherstan the characteristic of Lgong Keraton that exists within the scope of traditional Legong and its develomant into the creations of L egong. Legong maker use of various dance clements such as theme, structure of the dance, percussion patterns, and fashionabele make-up applien by the dancers. These elements are so interwined that L egong can be identified as a form of dace that has a sfecifikc content and reflects the elements are so intertwined that Legong can be ideniified as a form of dance that has a specific content and reflects the beauty of Balinese culture.